Frontal Fibrosing Alopecia: A Comprehensive Guide for Cosmetic Dermatologists - Marina Landau; Sofia M. Perez; Antonella Tosti (Dermatology and Therapy)
Abstract Frontal fibrosing alopecia (FFA) is an inflammatory, scarring hair loss that commonly affects postmenopausal women and presents as frontal hairline recession, facial papules, loss of eyebrows, and facial hyperpigmentation. Because of the chronic, progressive nature of this disease and its important impact on aesthetic appearance, patients often consult dermatologists to improve unwanted FFA symptoms. Cosmetic practices including the use of non-ablative lasers, autologous fat injections, and oral isotretinoin can improve FFA-associated facial vein prominence, atrophic indentations, and facial papules, respectively. On the other hand, while exact etiology underlying FFA development remains unclear, some procedures including deep chemical peels and ablative laser therapies have been shown to induce facial scarring and are contraindicated in patients with FFA. In the same way, some cosmetic ingredients can possibly be a triggering or worsening factor for FFA as well. Therefore, it is essential for dermatologists to be aware of both the benefits and risks of cosmetic treatments in patients with diagnosed or suspected FFA. This comprehensive review aims to outline the key cosmetic products and procedures that may be useful in patients with FFA and those which should be considered contraindicated.